The Endoplasmic Reticulum Role in the Plant Response to Abiotic Stress - Reyes-Impellizzeri, Sofía; Moreno, Adrian A. (Frontiers in Plant Science, 2021)
The endoplasmic reticulum (ER) is the organelle where one third of the proteins of a cell are synthetized. Several of these proteins participate in the signaling and response of cells, tissues, or from the organism to the environment. To secure the proper synthesis and folding of these proteins, or the disposal of unfolded or misfolded proteins, the ER has different mechanisms that interact and regulate each other. These mechanisms are known as the ER quality control (ERQC), ER-associated degradation (ERAD) and the unfolded protein response (UPR), all three participants of the maintenance of ER protein homeostasis or proteostasis. Given the importance of the client proteins of these ER mechanisms in the plant response to the environment, it is expected that changes or alterations on their components have an impact on the plant response to environmental cues or stresses. In this mini review, we focus on the impact of the alteration of components of ERQC, ERAD and UPR in the plant response to abiotic stresses such as drought, heat, osmotic, salt and irradiation. Also, we summarize findings from recent publications looking for a connection between these processes and their possible client(s) proteins. From this, we observed that a clear connection has been established between the ERAD and UPR mechanisms, but evidence that connects ERQC components to these both processes or their possible client(s) proteins is still lacking. As a proposal, we suggest the use of proteomics approaches to uncover the identity of these proteins and their connection with ER proteostasis.